Ad Hoc Manpower Study No. 1 Study on the Training of Skilled Craftsman (Working Papers-Volume I) - Institute of Applied Manpower Research (Institute of Applied Manpower Research)
In the course of discussions relating to the settlement of the two-year Research Programme of the I.A.M.R, the Directorate General of Employment and Training had urged that Manpower Group Survey (decided upon as the first major item of the programme) should not be limited (as originally proposed) to Engineering Graduates and Diploma holders only and that the scope of this study should be extended to cover the problems of planned development of facilities for training skilled craftsmen for industry.